Indigo degradation with laccases from Polyporus sp. and Sclerotium rolfsii - Campos, Rui (2001)
The degradation of the textile dye indigo with purified laccases from the fungi Trametes hirsuta (THL1 and THL2) and Sclerotium rolfsii (SRL1) was studied. All laccases were able to oxidize indigo yielding isatin (indole-2,3-dione), which was further decomposed to anthranilic acid (2-aminobenzoic acid). Based on the oxygen consumption rate of the laccases during indigo degradation, a potential mechanism for the oxidation of indigo involving the step-wise abstraction of four electrons from indigo by the enzyme was suggested. Comparing the effect of the known redox-mediators acetosyringone, 1-hydroxybenzotriazole (HOBT) and 4-hydroxybenzenesulfonic acid (PHBS) on laccase-catalyzed degradation of indigo, we found a maximum of about 30% increase in the oxidation rate of indigo with SRL1 and acetosyringone. The particle size of indigo agglomerates after laccase treatment was influenced by the origin of the laccase preparation and by the incubation time. Diameter distributions were found to have one maximum and compared to the indigo particle size distribution of the control, for all laccases, the indigo agglomerates seemed to have shifted to smaller diameters. Bleaching of fabrics by the laccases (based on K/S values) correlated with the release of indigo degradation products.